"One country, two histories": how PRC and western narratives of Chinese modernity diverge. (1st June 2020) - Horesh, Niv
Abstract : Held in October 2017, the 19th Chinese Communist Party (CCP) Congress enshrined not just Xi Jinping's grip on power. It also re-coated its ideology with a medley of Socialist and traditionalist buzz words that had been marginalized in the 1980s. During the height of the reform era, these increasingly made way for ideas borrowed from market economies. Predictably enough, the ideological ferment surrounding the 19th Party Congress has since also played out in the realm of education. This article examines in detail the most current history textbooks used in PRC classrooms to construe China's recent past. To that end, included in my exploration will not just be changing PRC attitudes to Chinese modern history, but also PRC instruction of world history. In passing, I will also compare the school material with the latest authoritative Western scholarly studies of the same topics by way of eliciting how PRC official historical narratives of 19th–20th century events diverge from Western ones. A better understanding of those narratives is crucial to predicting how the PRC will behave on the world stage as an emerging global superpower.